Efikasi Diri dan Strategi Koping Pada Penyesuaian Diri Dokter Muda - Agung Adhya Monacika; Supriyadi Supriyadi (Jurnal Studia Insania, 2021)
Self-adjustment is a process that involves mental response and an individual’s behaviour to be able to respond and resolve any complications. An individual who successfully counterbalances between their need and their environmental demands will adapt well without resistance. This study wants to identify the effect of self-efficacy and strategy focus coping within self-adjustment of co-assistant doctors in the work environment of central public health (RSUP) Sanglah. The subject of this quantitative research involves 82 co-assistant doctors Medical Education Department of Medical Faculty of Udayana University, a co-assistant doctor in RSUP Sanglah and that was chosen through simple random sampling. The instruments in this research are the self-efficacy scale with the reliability of 0,935. A strategy focused coping scale with the reliability of 0,908 and a self-adjustment scale of 0,886. Multiple regression analysis results show that self-efficacy and strategy focused coping have affected co-assistant doctor self-adjustment by 38,3%.